2008
DOI: 10.1113/jphysiol.2008.163154
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hyperpolarization‐activated current Ih in somatosensory neurons

Abstract: The hyperpolarization-activated current (I h ) is an inward current activated by hyperpolarization from the resting potential and is an important modulator of action potential firing frequency in many excitable cells. Four hyperpolarization-activated, cyclic nucleotide-modulated subunits, HCN1-4, can form I h ion channels. In the present study we investigated the function of I h in primary somatosensory neurons. Neuronal firing in response to current injection was promoted by elevating intracellular cAMP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
153
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 67 publications
21
153
2
1
Order By: Relevance
“…Cyclic nucleotide sensitivity applies in particular to HCN2 and HCN4 channels that are expressed in small sensory neurons, whereas HCN1 channels dominate in the larger-size neurons and are not facilitated by cyclic nucleotides but by low extracellular pH (443,507,675). In cultured rat DRG neurons, PGE 2 increased action potential frequency elicited by a current pulse and induced a depolarizing shift in the resting potential with both effects being antagonized by a specific I h blocker but remaining largely unaltered by a PKA inhibitor suggesting a role for HCN2 and HCN4 channels (506). A contribution of I h to various nociceptive manifestations of neuropathic pain and also mild heat injury has been established raising the possibility that HCN channels may have a significant role in actions of prostanglandins on peripheral nociceptive nerve terminals (97,174,445,506 , and Ca 2ϩ in small cultured DRG neurons of neonatal rats (106).…”
Section: C) Hyperpolarization-activated Cyclic Nucleotide-gatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic nucleotide sensitivity applies in particular to HCN2 and HCN4 channels that are expressed in small sensory neurons, whereas HCN1 channels dominate in the larger-size neurons and are not facilitated by cyclic nucleotides but by low extracellular pH (443,507,675). In cultured rat DRG neurons, PGE 2 increased action potential frequency elicited by a current pulse and induced a depolarizing shift in the resting potential with both effects being antagonized by a specific I h blocker but remaining largely unaltered by a PKA inhibitor suggesting a role for HCN2 and HCN4 channels (506). A contribution of I h to various nociceptive manifestations of neuropathic pain and also mild heat injury has been established raising the possibility that HCN channels may have a significant role in actions of prostanglandins on peripheral nociceptive nerve terminals (97,174,445,506 , and Ca 2ϩ in small cultured DRG neurons of neonatal rats (106).…”
Section: C) Hyperpolarization-activated Cyclic Nucleotide-gatedmentioning
confidence: 99%
“…In cultured rat DRG neurons, PGE 2 increased action potential frequency elicited by a current pulse and induced a depolarizing shift in the resting potential with both effects being antagonized by a specific I h blocker but remaining largely unaltered by a PKA inhibitor suggesting a role for HCN2 and HCN4 channels (506). A contribution of I h to various nociceptive manifestations of neuropathic pain and also mild heat injury has been established raising the possibility that HCN channels may have a significant role in actions of prostanglandins on peripheral nociceptive nerve terminals (97,174,445,506 , and Ca 2ϩ in small cultured DRG neurons of neonatal rats (106). Sensitization manifested itself as a decrease in activation threshold and a leftward shift of the pressure-activity curve, and it was mediated by the cAMP-PKA pathway.…”
Section: C) Hyperpolarization-activated Cyclic Nucleotide-gatedmentioning
confidence: 99%
“…These effects appear to be due, in part, to changes in hyperpolarization-activated, cyclic nucleotide-regulated channel (HCN) channel expression and function. First, in situ hybridization (Kouranova et al, 2008), immunohistochemical (Tu et al, 2004;Jiang et al, 2008;Kouranova et al, 2008), and electrophysiological (Mayer and Westbrook, 1983;Kouranova et al, 2008;Momin et al, 2008) data show that sensory neurons express HCN channels, and that injury causes altered HCN subunit trafficking (Chaplan et al, 2003;Jiang et al, 2008) and enhanced I H current amplitudes (Chaplan et al, 2003;Yao et al, 2003). Second, sensory cell hyperexcitability is inhibited by superfusion with N-ethyl-1,6-dihydro-1,2-dimethyl-6-(methylimino)-N-phenyl-4-pyrimidinamine hydrochloride (ZD7288) (Chaplan et al, 2003;Yao et al, 2003;Jiang et al, 2008), a selective pan-isoform inhibitor of HCN channels, and systemic, but not central, administration of ZD7288 alleviates mechanical allodynia (Chaplan et al, 2003;Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpolarisation-evoked current can be enhanced by cAMP and, to a lesser extent, by cGMP by direct binding to a C-terminal site, which causes a shift in channel activation to more positive membrane potentials [249]. Voltage-clamp studies in DRG neurones showed that large neurones expressed a fast, cAMP-insensitive I h in large neurones, and that this current was abolished by genetic deletion of HCN1, while in small neurones a slower, cAMP-sensitive current, consistent with expression of HCN2, was seen [250]. In small neurones the enhanced generation of action potentials caused by exposure to PGE 2 was found to be entirely attributable to the cAMP-sensitivity of I h , and other factors such as modulation of Na currents (see above) played at most a marginal role [250].…”
Section: Hcn Channelsmentioning
confidence: 99%